Peningkatan Daya Saing UMKM Melalui Penguatan Legalitas Usaha di Kota Payakumbuh - Inggrit Fernandes; Sri Aisyah; Amelia Zulfitri; Felia Hermayenti; Refa Swinta Maharani (Jurnal Pengabdian Pendidikan Masyarakat (JPPM), 2026)
UMKM play a vital role in a regional economy. However, many MSMEs in Payakumbuh City still face significant obstacles, particularly in terms of business legality, characterized by low levels of Business Identification Number (NIB). This situation hinders competitiveness, banking access, and business development opportunities. This community service activity aims to strengthen the legality of MSMEs through education and technical assistance. The method used is a participatory and collaborative approach, involving three main stages: a Business Law Education Workshop, an UMKM Legal Clinic (direct assistance in obtaining a NIB through the Online Single Submission/OSS system), and a Collaborative Discussion with local stakeholders. The results of the activity showed significant improvements, with 11 participants successfully obtaining a NIB and an increase in legal understanding that encouraged independent legal registration. This success proves that technical obstacles and lack of understanding can be overcome with appropriate assistance, resulting in an effective community-based legal assistance model. Thus, this legal strengthening contributes significantly to increasing the administrative capacity and competitiveness of UMKM in Payakumbuh.